Errors in Surgical Site Identification during Cutaneous Surgery for Skin Cancer: Review and Recommendations - Paul, Sharad P. (Scientific Research, 2015)
Surgical error due to incorrect identification of the surgical site has been known to occur right from the beginning of surgical practice through the ages. However, increasing awareness, preventative efforts and risks of litigation have not eliminated this problem. Cutaneous surgery for skin cancer makes up a large proportion of procedures performed each year and it is often difficult to correctly identify biopsy sites, especially as this is not easy in sun-damaged skin. In this review article, we review the incidence of wrong-site surgery, measures taken by professional bodies, and the use of photography and newer technologies in an attempt to eliminate this distressing event in the field of plastic and dermatologic surgery. The purpose of this review is to highlight the incidence of such surgical site identification errors, evaluate the risk factors, and educate the surgeon about measures that can be undertaken to avoid being faced with such a situation.
Keywords: Skin Cancer; Medical Error; Patient Safety; Dermatology; Wrong Site Surgery; Melanoma